YouTube as digital public sphere: Controversary over Indonesia’s Military Reform Law - Putri, Lutfiani Sayyida Eka; Lestari, Kalimah Wasis; Payo, Nadia; Ambardo, Marsha; Nareshwari, Syalsabila Amalia; Aqila, Ratu Sakinatul; Cahyani, Eylin Intan Regita; Sahara, Berliana Elsa (Universitas Airlangga, 2025)
The issue of revising the TNI Law has been considered an offense against the principles of democracy and civil supremacy, triggering fears of the military's dual function (including involvement in socio-political affairs), as seen during Suharto's New Order era. This research aims to analyze the pros and cons of the audience of the Bocor Alus Politik YouTube channel towards the Revision of the Indonesian National Army Law (RUU TNI) through the comments of the content titled